Flashcards in Block 2 Deck (17)

Loading flashcards...

1

## Absolute value inequality form [A] < c is equivalent to:

###
- c < A < c

"(-) negative c is LESS THAN A which is LESS THAN c"

2

## Absolute value inequality form [A] = c is equivalent to:

###
- c = A = c

"(-) negative c is LESS than or EQUAL to A which is LESS than or EQUAL to c"

3

## Absolute value inequality form [A] > c is equivalent to:

###
A < - c

"A is LESS THAN (-) negative c"

OR

A > c

"A is GREATER THAN c"

(duh this is the form given just without the absolute value)

4

## Absolute value inequality form [A] >/= c is equivalent to:

###
A = -c

"A is LESS than or EQUAL to (-) negative c"

OR

A >/= c

"A is GREATER than or EQUAL to c"

(duh this is the form given just without the absolute value)

5

## What is an Absolute Value?

### The distance from 0 on the number line

6

## [u] < k is equivalent to:

### - k < u < k

7

## [u] > k is equivalent to:

###
u < -k

OR

u > k (the form given)

8

## What form will you give your answer in if it says Interval Notation?

###
The ( , ) or [ , ] to determine inclusive or not

With infinities if needed

9

##
y = f(x)

How are you going to transform it to:

y = af(x)

###
- Multiply y-coords by a

This will result in VERTICAL stretching/shrinking

10

##
y = f(x)

How are you going to transform it to:

y = f(ax)

###
- Divide x-coords by a

This will result in HORIZONTAL stretching/shrinking

11

##
y = f(x)

How will you reflect it to:

y = - f(x)

### Reflect over the x-axis

12

##
y = g(x)

How will you reflect it to:

y = g(-x)

### Reflect over the y-axis

13

## What is the formula for finding DISTANCE between two points on a graph?

###
d = Square root of:

(x2 - x1)^2 + (y2 - y1)^2

14

## What is the formula for finding the MIDPOINT of a segment?

### (x1 + x2 / 2 , y1 + y2 / 2)

15

## What is the standard equation of a circle?

### (x - h)^2 + (y - k)^2 = r^2

16

## If you are given the Center and Radius of a circle, how will you find the Circle's Equation?

###
Plug and chug (h , k) and r

(x - h)^2 + (y - k)^2 = r^2

17